Breaking down the monolith: Understanding flu vaccine uptake among African Americans - Sandra Crouse Quinn; Amelia Jamison; Ji An; Vicki S. Freimuth; Gregory R. Hancock; Donald Musa (Elsevier, 2018)
Black adults are significantly less likely to be immunized for seasonal influenza when compared to Whites. This persistent disparity contributes to increased influenza-related morbidity and mortality in the African American population. Most scholarship on vaccine disparities has compared Whites and Blacks. Employing Public Health Critical Race Praxis, this study seeks to shift the focus to explore differences within the Black population. Utilizing a nationally-representative 2015 survey of US Black adults (n = 806), we explore differences by gender, age, income, and education across vaccine-related measures (e.g., perceived risk, knowledge, attitudes) and racial factors (e.g. racial salience, racial fairness, perceived discrimination). We also explore differences by vaccine behavior in the past five years among those who vaccinate every year, most years but not all, once or twice, and never. Greater frequency of flu vaccine uptake was associated with better self-reported vaccine knowledge, more positive vaccine attitudes, more trust in the flu vaccine and the vaccine process, higher perceived disease risk, lower perceived risk of vaccine side effects, stronger subjective and moral norms, lower general vaccine hesitancy, higher confidence in the flu vaccine, and lower perceived barriers. Logistic regression results highlighted other significant differences among the groups, emphasizing areas to target for improved vaccination rates. We find great diversity within the Black community related to influenza immunization decisions, highlighting the need to "break down the monolith" in future research.